2021
DOI: 10.1021/acs.energyfuels.1c02201
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Degassing Time and Temperature on the Estimation of Pore Attributes in Shale

Abstract: The influence of degassing time and temperature on low-pressure gas adsorption (LPGA) behavior of shales was examined in this study. Two organic-rich shales of contrasting maturity, reactivity and organic matter type, were crushed to <1 mm and <212 μm grain-sizes and degassed at 110, 200, and 300 °C for 3 and 12 h, respectively. Our results indicate that degassing duration has a minimal influence on pore-character interpretations from LPGA experiments, while the degassing temperature shows a strong influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Low-temperature subcritical physisorption studies are used routinely to characterize the porous structures of a wide range of materials. In the case of shales and kerogens, it is essential to ensure that representative sampling is undertaken for an appropriate particle size range and that degassing conditions are precisely controlled. Most of the adsorption research for both sub- and supercritical adsorption has used samples, which have been degassed under a high vacuum at 383 K, so that all adsorbed water vapor and CO 2 were removed. ,,, This temperature was used to ensure the removal of adsorbed water without significant modification of the shale structure and gives a baseline for adsorption measurements for a dry sample.…”
Section: Adsorption Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-temperature subcritical physisorption studies are used routinely to characterize the porous structures of a wide range of materials. In the case of shales and kerogens, it is essential to ensure that representative sampling is undertaken for an appropriate particle size range and that degassing conditions are precisely controlled. Most of the adsorption research for both sub- and supercritical adsorption has used samples, which have been degassed under a high vacuum at 383 K, so that all adsorbed water vapor and CO 2 were removed. ,,, This temperature was used to ensure the removal of adsorbed water without significant modification of the shale structure and gives a baseline for adsorption measurements for a dry sample.…”
Section: Adsorption Methodsmentioning
confidence: 99%
“…32−35 Most of the adsorption research for both sub-and supercritical adsorption has used samples, which have been degassed under a high vacuum at 383 K, so that all adsorbed water vapor and CO 2 were removed. 12,13,34,36 This temperature was used to ensure the removal of adsorbed water without significant modification of the shale structure and gives a baseline for adsorption measurements for a dry sample.…”
Section: Concept Of Gibbs Surface Excessmentioning
confidence: 99%
“…Organic-hosted porosity is one of the most critical elements in successful shale plays. Different techniques viz., imaging (e.g., broad ion beam-scanning electron microscopy, and focused ion beam-scanning electron microscopy), gas adsorption (low pressure and high pressure gas adsorption techniques), mercury intrusion porosimetry, neutron scattering (e.g., ultrasmall/small angle neutron scattering), etc., are used to assess shale porosity. ,,, In addition to several factors, such as the presence of surface functional groups, the mesopores and micropores, and the specific surface area, etc., thermal maturity levels have been identified to strongly control the development of organic porosity and, hence, the gas adsorption capacity of shales and carbonaceous matter. Loucks et al observed organic nanopore development to be strongly dependent on the thermal maturity levels of the samples and inferred that this is essentially caused by the conversion of kerogen to hydrocarbons and the formation of pores within the organic matter in the process.…”
Section: Co2 Adsorption Versus Ch4 Desorption: Vis-à-vis Co2 Sequest...mentioning
confidence: 99%
“…Different pretreatment methods have a significant influence on the measured results. Different pretreatment methods have a significant influence on the measured results . Low-temperature nitrogen adsorption experimental process was carried out in accordance with GB/T 21650.2-2008 (determination of pore size distribution and porosity of solid materials by the mercury intrusion method and gas adsorption method) in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Different pretreatment methods have a significant influence on the measured results. 53 Low-temperature nitrogen adsorption experimental process was carried out in accordance with GB/T 21650.2-2008 (determination of pore size distribution and porosity of solid materials by the mercury intrusion method and gas adsorption method) in this study. Before the test, the samples were dried (120 °C, 24 h) and then degassed ( Note: I is illite; S is smectite; I/S is illite/smectite interlayer; %S is interlayer ratio; C is chlorite.…”
Section: Samples and Methodsmentioning
confidence: 99%